Understanding Chinese Cities. Redesigning italian methods - Li Bao; Marco Trisciuoglio (Agathón)
What could be the outcomes of an urban regeneration project in China nowadays? Should we really choose between ordinary districts composed of tall, anonymous buildings or gated communities closed into inner villages and dominated by fake restorations in the traditional Chinese style? In the contemporary Chinese society, with the economic system becoming more and more complex along with the new rules concerning ownership, all these novelties demand designers and decision-makers to find a third way, namely, the new sustainable architecture that is designed based on the typological and morphological fundamentals of the city. That is also a way for the necessary renovation of typological and morphological studies into the architectural and urban worldwide culture towards much less rigid and much more flexible ideas of what a type is. The paper describes the teaching experience of two architectural design professors (one Chinese and one Italian) in Nanjing at SEU Arch during the last four years.